Análisis y evaluación de la cartera de crédito en el Sistema Financiero Popular y Solidario del segmento 3 de la ciudad de Loja, periodo 2019-2020Análisis y evaluación de la cartera de crédito en el Sistema Financiero Popular y Solidario del segmento 3 de la ciudad de Loja, periodo 2019-2020 - Mejía Parra, Favián Wladimir (2022)
The Popular and Solidarity Financial System makes an essential contribution to the economy, because of the dynamism it provides based on financial intermediation. Nevertheless, the economic crisis and the health emergency caused by the COVID-19 pandemic have meant that Cooperatives of Savings and Credit of segment 3 will have the inconvenience of recovering their assets invested, in the emergency credit portfolio, their financial indicators of: profitability, delinquency and liquidity, also the provisions of the credit portfolio according to the stipulated risk levels. by the Monetary and Financial Policy and Regulation Board. In this context, the investigation analyzes three Savings and Credit Cooperatives of Segment 3 of the City of Loja, where it was possible to determine: the structure of the credit portfolio, its level of delinquency, the financial impact caused by the provisions made and the level of risk reached by the risk portfolio in the study period 2019 and 2020.